Senescent T-Cells Promote Bone Loss in Rheumatoid Arthritis - Fessler, Johannes; Husic, Rusmir; Schwetz, Verena; Lerchbaum, Elisabeth; Aberer, Felix; Fasching, Patrizia; Ficjan, Anja; Obermayer-Pietsch, Barbara; Duftner, Christina; Graninger, Winfried; Stradner, Martin Helmut; Dejaco, Christian (Frontiers in Immunology, 2018)
Objective: T-cells are critical players in the pathogenesis of osteoporosis in patients with rheumatoid Arthritis (RA). Premature senescence of lymphocytes including accumulation of senescent CD4+ T-cells is a hallmark feature of RA. Whether T-cell senescence is associated with bone loss in RA patients is elusive so far. Methods: Prospective study of consecutive patients with RA (n=107), patients with primary osteopenia/-porosis (n=75) and healthy individuals (n=38). Bone mineral density (BMD) was determined by dual energy X-ray absorptiometry (DXA) scan. Flow cytometry, magnetic-associated cell sorting and cell culture experiments were performed to analyze the pro-osteoclastic phenotype and function of senescent CD4+CD28- T-cells. Results: Patients with osteopenia/-porosis yielded a higher prevalence of senescent CD4+CD28- T-cells than individuals with normal BMD, in the RA as well as in the non-RA cohort. RANKL was expressed at higher levels on CD4+CD28- T-cells as compared to CD28+ T-cells. Stimulation with IL-15 led to an upregulation of RANKL expression, particularly on CD28- T-cells. CD4+CD28- T-cells induced osteoclastogenesis more efficiently than CD28+ T-cells. Conclusion: Our data indicate that senescent T-cells promote osteoclastogenesis more efficiently than conventional CD28+ T-cells, which might contribute to the pathogenesis of systemic bone loss in RA and primary osteoporosis.